Production, fuel properties and combustion testing of an iso-olefins blendstock for modern vehicles. (15th February 2022) - Dagle, Vanessa Lebarbier; Affandy, Martin; Lopez, Johnny Saavedra; Cosimbescu, Lelia; Gaspar, Daniel J.; Scott Goldsborough, S.; Rockstroh, Toby; Cheng, Song; Han, Taehoon; Kolodziej, Christopher P.; Hoth, Alexander; Majumdar, Sreshtha Sinha; et al.
Highlights: A dimethyl-hexenes rich olefins mixture (DMHROM) for gasoline engines. A pathway for DMHROM production from ethanol was developed and scaled up. DMHROM presents high potential to meet gasoline ASTM D4814 specifications. Dimethyl-hexenes have potential to improve engine efficiency and fuel economy. Abstract: With the increasing pressure to decarbonize the transportation sector, exploring strategies that can reduce emissions from light-duty vehicles (LDV) has become critical. Bioblendstocks that allow for higher engine efficiency and fuel economy could complement vehicle electrification and help reach carbon neutrality by 2050. In this context, the potential of a mixture of iso-olefins as a bioblendstock was investigated for multimode boosted spark-ignition (SI)/advanced compression ignition (ACI) engine operation designed to achieve higher overall vehicle fuel economy. By establishing the relationship between the molecular structure of iso-olefins and research octane number (RON), octane sensitivity (S) (i.e., the difference between RON and motor octane number [MON]), and phi-sensitivity (i.e., the sensitivity of autoignition to the fuel-air equivalence ratio) a dimethyl-hexenes rich olefins mixture (DMHROM) was identified as a preferred blendstock for SI/ACI combustion engines. A pathway for DMHROM production from biomass-derived ethanol was developed and scaled up. More than 1 gallon of DMHROM blendstock was produced for fuel properties assessment including engine testing. Measurements in a Cooperative Fuel Research Engine showed that the DMHROM blendstock possesses a RON of 94 and S of 13.5, and blends synergistically. Rapid compression machine tests coupled with single-cylinder gasoline direct injection engine measurements demonstrated the 20 vol% DMHROM blend has higher phi-sensitivity than an olefin-free gasoline base fuel and a typical California Reformulated Gasoline Blendstock for Oxygenate Blending (CARBOB) gasoline fuel. These results demonstrate the potential of DMHROM for improving gasoline fuel performance and quality for operation under ACI conditions. The effectiveness of the aftertreatment system in mitigating emissions was verified and showed that the pure DMHROM blendstock and 20 vol% blend would not increase non-methane organic gases, NOx, or carbon monoxide (CO) emissions. The DMHROM blendstock was found to slightly decrease sooting tendency when added to a gasoline-base fuel (i.e., ∼6% reduction at 20 vol% blending level). Oxidation stability and lubricant compatibility were both confirmed for the 20 vol% blend. Overall, these results demonstrate that dimethyl-hexenes have potential for improving engine efficiency and fuel economy while meeting emissions regulations and ASTM specifications for gasoline fuel.